Actividad antimicrobiana de extractos de tallos y flores del Hedyosmum sp. recolectadas en el bosque Jacarón, Chimborazo. Octubre 2018- febrero 2019 - Valarezo Flores, Stefanye Anahy (2019)
Throughout history, medicinal plants have had an invaluable potential and information about their role in the prevention and cure of diseases has been transmitted from generation to generation. The bioactive compounds of medicinal plants are studied extensively. The objective of this research was to determine the antibacterial activity of hexanic extracts of flowers and stems of the plant species Hedyosmum sp. against strains ATCC Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus and Enterococcus faecalis. The dried parts of the plant were milled and macerated in hexane for 72 hours, and the extracts were filtered, rotaevaporated and concentrated. Using the Kirby Bauer method, the antibacterial activity of the hexane extracts was tested at concentrations of 500,000, 250,000, 125,000, 62,500 and 31,250 μg / mL from a concentrated solution. The yields of stems and flowers extracts were 0.9% and 1.79%, respectively. The activity showed by the extracts was higher than the Gram negative bacteria, with P. aeruginosa being the most sensitive to these, since a MIC value of 31,250 μg / mL was obtained for both, lower than those found against E. coli and K. pneumoniae. The effect observed against the Gram positive bacteria tested indicated that the extracts are little or not active at the tested concentrations since only S. aureus was sensitive to the action of the extract of the flowers (MIC 250,000 μg / mL). These hexanic extracts could be natural sources of antibacterial compounds.